2013
DOI: 10.1021/jf400767d
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Characterization of Aptamers against Salmonella typhimurium Using Whole-Bacterium Systemic Evolution of Ligands by Exponential Enrichment (SELEX)

Abstract: In this paper, a high-affinity ssDNA aptamer binding to Salmonella typhimurium was obtained by a whole-bacterium-based Systemic Evolution of Ligands by Exponential Enrichment (SELEX) procedure. After nine rounds of selection with S. typhimurium as the target, a highly enriched oligonucleotide pool was sequenced and then grouped into different families based on primary sequence homology and secondary structure similarity. Eleven sequences from different families were selected for further characterization via fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(87 citation statements)
references
References 25 publications
(36 reference statements)
1
86
0
Order By: Relevance
“…LOD is 3 CFU/ml in bacterial suspension.Ma et al (2014)   S. typhimurium whole   live cellsDNASandwich-type system with fluorescent detection. LOD is 25 CFU/ml in bacterial suspension.Duan et al (2013a)   S. typhimurium whole   live cellsDNAImpedimetric aptasensor. LOD is 600 CFU/ml in bacterial suspension.Labib et al (2012b) and Kolovskaya et al (2013)   S. enteritidis whole   live cellsDNAImpedimetric biosensor.…”
Section: Antiviral Aptamersmentioning
confidence: 99%
“…LOD is 3 CFU/ml in bacterial suspension.Ma et al (2014)   S. typhimurium whole   live cellsDNASandwich-type system with fluorescent detection. LOD is 25 CFU/ml in bacterial suspension.Duan et al (2013a)   S. typhimurium whole   live cellsDNAImpedimetric aptasensor. LOD is 600 CFU/ml in bacterial suspension.Labib et al (2012b) and Kolovskaya et al (2013)   S. enteritidis whole   live cellsDNAImpedimetric biosensor.…”
Section: Antiviral Aptamersmentioning
confidence: 99%
“…sigmaaldrich.com). The aptamers used in our research were prepared in our laboratory using previously reported methods [26,27]. Bacteria aptamers were synthesized by the Shanghai Sangon Biological Science & Technology Company (Shanghai, China) (http://www.sangon.com).…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…The S. typhimurium aptamer were prepared in our laboratory. 26 The sequence of S. typhimurium aptamer is 5′-SH-ATAGGAGTCACGACGAC-CAGAAAGTAATGCCCGGTAGTTATTCAAAGATGAGTAG-GAAAAGATATGTGCGTCTACCTCTTGACTAAT-3′ (apt1), and 5′-Bio-ATAGGAGTCACGACGACCAGAAAGTAATGCC-CGGTAGTTATTCAAAGATGAGTAGGAAAAGATATGTGC-GTCTACCTCTTGACTAAT-3′ (apt2), synthesized by the Shanghai Sangon Biological Science & Technology Company (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%